2016
DOI: 10.7860/jcdr/2016/13241.7669
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Periodontitis Using Chlorhexidine Chip and Diode Laser-A Clinical Study

Abstract: Introduction: The use of adjuncts like chlorhexidine local delivery and diode laser decontamination have been found to improve the clinical outcomes of scaling and root planing in non-surgical periodontal therapy in patients with chronic periodontitis. Aim:To evaluate the effects of diode laser and chlorhexidine chip as adjuncts to scaling and root planing in the management of chronic periodontitis. The objective is to evaluate the outcome of chlorhexidine chip and diode laser as adjuncts to scaling and root p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
(10 reference statements)
0
18
1
Order By: Relevance
“…The evidence supports the adjunctive use of local antimicrobials with subgingival debridement at deep or recurring periodontal sites, mainly with the use of sustained release antimicrobial vehicles 43 . Unlike the other authors, Jose et al 2016 44 compared the effects of a laser diode and a chlorhexidine chip used alone and in combination with scaling and root planing in the management of chronic periodontitis. After treatment, the test and control sites showed a statistically significant reduction in PI, GI and pocket depth (PPD).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence supports the adjunctive use of local antimicrobials with subgingival debridement at deep or recurring periodontal sites, mainly with the use of sustained release antimicrobial vehicles 43 . Unlike the other authors, Jose et al 2016 44 compared the effects of a laser diode and a chlorhexidine chip used alone and in combination with scaling and root planing in the management of chronic periodontitis. After treatment, the test and control sites showed a statistically significant reduction in PI, GI and pocket depth (PPD).…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered that the authors have used the power of 0.5 W for 10 seconds, which may not be adequate. (19) Nguyen et al assessed the effect of 940 nm diode laser and found no significant effect on PD compared to treatment with SRP alone. It should be noted that in this study, laser irradiation and SRP were performed simultaneously, and that power of 0.8 W may be insufficient for therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…(15) In a study about gingivitis, Jose et al did not observe a significant difference between laser group irritated with the wavelength of 810 nm and control group in terms of decreasing GI, which can be caused by irradiation settings (power of 0.5 W for 10 seconds). (19) Previous studies have shown that laser radiation can affect the production of cytokines and growth factors, and thereby can accelerate the recovery. (3,6,25) Üstün et al showed that the use of 810 nm diode laser can cause significant decrease in the amount of GCF and IL-1β compared to control group, which could be an explanation for the decrease in GI and PD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations